El derecho de explotación en las concesiones de infraestructura vial en el Perú: relevancia, riesgos y casos críticos - Paz Sime, Miguel Angel (2025)
In this article, the author examines the right to operate under road infrastructure concessions in Peru within the context of Public-Private Partnerships. He analyzes how this right, primarily exercised through toll collection, is essential to the economic equilibrium of concession projects. The author also discusses the problems that arise when the Government violates the operational rights, whether through political or legislative decisions. The author highlights the legal and contractual implications of these violations, including claims for non-compliance and compensation mechanisms, with a focus on legal certainty and investment protection.